Denitrifying anaerobic methane-oxidizing bacteria in river networks of the Taihu Basin: Community dynamics and assembly process - Wang, Ruyue; Xu, Sai; Zhu, Yuxiang; Zhang, Tao; Ge, Shijian (Frontiers in Microbiology, 2022)
Denitrifying anaerobic methane-oxidizing bacteria (DAMO bacteria) plays an important role in reducing methane emissions from river ecosystems. However, the assembly process of their communities underlying different hydrologic seasons remains unclarified. In this study, the dynamics of DAMO bacterial communities in river networks of the Taihu Basin were investigated by amplicon sequencing across wet, normal, and dry seasons followed by multiple statistical analyses. Phylogenetic analysis showed that Group B was the major subgroup of DAMO bacteria and significant dynamics for their communities were observed across different seasons (constrained principal coordinate analysis, p = 0.001). Furthermore, the neutral community model and normalized stochasticity ratio model were applied to reveal the underlying assembly process. Stochastic process and deterministic process dominated the assembly process in wet season and normal season, respectively and similar contributions of deterministic and stochastic processes were observed in dry season. Meanwhile, abundant (relative abundance >0.1%) and rare (relative abundance <0.01%) DAMO bacterial communities were found to be shaped via distinct assembly processes. Deterministic and stochastic processes played a considerable role in shaping abundant DAMO bacterial communities, while deterministic process mainly shaped rare DAMO bacterial communities. Results of this study revealed the dynamics of DAMO bacterial communities in river networks and provided a theoretical basis for further understanding of the assembly process.